ANALISIS PROSES COMPUTATIONAL THINKING SISWA SEKOLAH DASAR MELALUI PENYELESAIAN SOAL MATEMATIKA OPEN ENDED - Putri Hanifah Suwarno; Khaysya Ikhrima Millatil Habibah; Adyva Nasha Permata Rahmadhani; Tamara Putri Ramadhani; Rissa Prima Kurniawati (Prosiding Konferensi Ilmiah Dasar, 2026)
Computational Thinking is an essential skill in mathematics learning that enables students to solve problems logically and systematically. This study aimed to describe the Computational Thinking process of elementary school students through solving open-ended mathematics problems on plane geometry. This study employed a descriptive qualitative approach involving five fourth-grade students of SDN Ngadirejo 02 selected through purposive sampling. Data were collected through a written test consisting of one open-ended problem and documentation, then analyzed using the Miles and Huberman model. The findings showed that students' Computational Thinking abilities varied across the four indicators. Two students achieved the decomposition indicator, while three students had not achieved it optimally. Four students met the pattern recognition and abstraction indicators, whereas one student had not. All students demonstrated the algorithmic thinking indicator. The findings indicate that decomposition was the most challenging indicator in solving open-ended mathematics problems.